2014
DOI: 10.1063/1.4868091
|View full text |Cite
|
Sign up to set email alerts
|

Ge interface engineering using ultra-thin La2O3 and Y2O3 films: A study into the effect of deposition temperature

Abstract: A study into the optimal deposition temperature for ultra-thin La2O3/Ge and Y2O3/Ge gate stacks has been conducted in this paper with the aim to tailor the interfacial layer for effective passivation of the Ge interface. A detailed comparison between the two lanthanide oxides (La2O3 and Y2O3) in terms of band line-up, interfacial features, and reactivity to Ge using medium energy ion scattering, vacuum ultra-violet variable angle spectroscopic ellipsometry (VUV-VASE), X-ray photoelectron spectroscopy, and X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 103 publications
8
32
0
Order By: Relevance
“…This is consistent with the YGeO x peak position of the previous reports. [ 20 ] However, there was no peak near ≈32.5 eV, which corresponded to the GeO 2 . This indicates that the interfacial layer formed through IOF and OPA was mostly the YGeO x layer with the minimal involvement of the GeO 2 formation, which is different from the previous report.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the YGeO x peak position of the previous reports. [ 20 ] However, there was no peak near ≈32.5 eV, which corresponded to the GeO 2 . This indicates that the interfacial layer formed through IOF and OPA was mostly the YGeO x layer with the minimal involvement of the GeO 2 formation, which is different from the previous report.…”
Section: Resultsmentioning
confidence: 99%
“…A substrate peak (Ge 3d 0 ) located at ~28.6 eV with additional peaks at higher binding energies in relation to the IL (consisting of Ge oxides and germanate) could be observed in all spectra. The Ge 3d 0 substrate peak is fitted with a doublet of Ge 3d 5/2 and Ge 3d 3/2 with spin-orbit splitting of 0.6 eV and intensity ratio of 3:2, respectively [18]. The Ge oxides (GeO x ) consist of four peaks (Ge 1+ , Ge 2+ , Ge 3+ , Ge 4+ ), which are at higher binding energy respect to the Ge 3d 0 with energy shifts of 0.8, 1.8, 2.6, and 3.4 eV, respectively [19].…”
Section: Resultsmentioning
confidence: 99%
“…The resulting oxygen-densification may suppresses GeO volatilization and maintains GeO 2 integrity and interface quality. 48 Mitrovic et al 51 reported on neutral oxygen vacancy coordinated with two Ge ions and Ge 2þ coordinated with two oxygen defects in sub-stoichiometric GeO x layer at the Y 2 O 3 /Ge interface which are disappearing when higher temperatures of 400 C are used for the growth of Y 2 O 3 by MBE. Similar mechanisms have to be taken into account for the annealed samples treated in this survey, which finally means that the chosen annealing parameters (high PDA temperature, longer annealing times) may effectively decrease the density of DB and OD at the oxide/Ge interface.…”
Section: B Xps Analysismentioning
confidence: 98%